Association between case volume and mortality in pre-hospital anaesthesia management: a retrospective observational cohort. (February 2022) - Saviluoto, Anssi; Jäntti, Helena; Kirves, Hetti; Setälä, Piritta; Nurmi, Jouni O.
Abstract: Background: Pre-hospital anaesthesia is a core competency of helicopter emergency medical services (HEMS). Whether physician pre-hospital anaesthesia case volume affects outcomes is unknown in this setting. We aimed to investigate whether physician case volume was associated with differences in mortality or medical management. Methods: We conducted a registry-based cohort study of patients undergoing drug-facilitated intubation by HEMS physician from January 1, 2013 to August 31, 2019. The primary outcome was 30-day mortality, analysed using multivariate logistic regression controlling for patient-dependent variables. Case volume for each patient was determined by the number of pre-hospital anaesthetics the attending physician had managed in the previous 12 months. The explanatory variable was physician case volume grouped by low (0–12), intermediate (13–36), and high (≥37) case volume. Secondary outcomes were characteristics of medical management, including the incidence of hypoxaemia and hypotension. Results: In 4818 patients, the physician case volume was 511, 2033, and 2274 patients in low-, intermediate-, and high-case-volume groups, respectively. Higher physician case volume was associated with lower 30-day mortality (odds ratio 0.79 per logarithmic number of cases [95% confidence interval: 0.64–0.98]). High-volume physician providers had shorter on-scene times (median 28 [25th–75th percentile: 22–38], compared with intermediate 32 [23–42] and lowest 32 [23–43] case-volume groups; P <0.001) and a higher first-pass success rate for tracheal intubation (98%, compared with 93% and 90%, respectively; P <0.001). The incidence of hypoxaemia and hypotension was similar between groups. Conclusions: Mortality appears to be lower after pre-hospital anaesthesia when delivered by physician providers with higher case volumes.